Special Economic Zones in the Emerging Economic Scenario: Issues and Challenges - Sharda, N. K.; Kumar, Raj; Chandel, Kulbhushan (Prabandhan: Indian Journal of Management, 2008)
Special economic zone is a "duty free enclave" that is to be treated as foreign territory for the operations of trade, duties and tariff. The SEZ are governed by special legislative policies and systems, which are otherwise not applicable in the country. The concept of special economic zones is a powerful instrument, which is designed to achieve the rapid growth in manufacturing, employment and export. It offers the only way in filling the gap between China, South East Asian nations and India in terms of manufacturing and employment. It is also an essential tool to attract foreign capital, technology and will help to integrate national economy with global economy. The main objective behind the establishment of special economic zones was to transform the agrarian economy into the industrial economy. In India the deliberations over the philosophy of the special economic zones was started in the year 2000. Finally, SEZ Act was passed in 2005 and notified on 10th Feb. 2006. In the present paper, an effort has been made to examine the government policy on SEZ and thereafter an attempt has been made to analyze critically the implications of SEZ in agricultural sector, food security situation, displacement of masses, fiscal deficit, external sector, social sector and labour laws. The last section of the paper deals with the concluding remarks and certain suggestions.